Volume 1: Fora, Parts a and B 2002
DOI: 10.1115/fedsm2002-31039
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Control of Vortex Breakdown by Pulsed Blowing Over a Delta Wing With Rounded Leading-Edge

Abstract: The purpose of this study is to construct and test an experimental device to control vortex on a delta wing. The model has a root chord of c = 690mm and a sweep angle of Λ = 60°. The control system is based on four rectangular slits 50 mm long and 0.2 mm wide running along the leading edge. This configuration produces jets normal to the leading edge. The mass flow rates and frequencies of injection can be varied independently. The results are shown in the form of surface flow visualizations, with the skin fric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…10 Direct numerical studies 14,15 on flow over cylinders have shown considerable reduction in lift variation by using suction to control the vortex shedding. There is a large literature dealing with pulsed and synthetic jets, [16][17][18][19][20] plasma discharge based actuation [21][22][23][24][25][26] for flow control applications resulting in increased lift-to-drag ratio.…”
Section: Introductionmentioning
confidence: 99%
“…10 Direct numerical studies 14,15 on flow over cylinders have shown considerable reduction in lift variation by using suction to control the vortex shedding. There is a large literature dealing with pulsed and synthetic jets, [16][17][18][19][20] plasma discharge based actuation [21][22][23][24][25][26] for flow control applications resulting in increased lift-to-drag ratio.…”
Section: Introductionmentioning
confidence: 99%